2001
DOI: 10.1007/s003300101135
|View full text |Cite
|
Sign up to set email alerts
|

Primary hydatid cyst in the retroperitoneal space: role of CT

Abstract: Localization of hydatid disease in the retroperitoneal space is extremely rare. We present the CT findings in a patient with echinococcal disease (E. Granulosus) in whom the cyst was localized to the retroperitoneum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Computed tomography or ultrasound guided needle biopsies also are helpful in diagnosis (12), although some authors do not recommend it because of the risk of cyst rupture and anaphylactic reaction could occur (9,11). Concerns over microscopic spillage at the time of needle biopsy do not appear warranted, especially if patient receive subsequent medical treatment and biopsy tracts are resected at the time of surgery (13).…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography or ultrasound guided needle biopsies also are helpful in diagnosis (12), although some authors do not recommend it because of the risk of cyst rupture and anaphylactic reaction could occur (9,11). Concerns over microscopic spillage at the time of needle biopsy do not appear warranted, especially if patient receive subsequent medical treatment and biopsy tracts are resected at the time of surgery (13).…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the patient presented with features of small gut obstruction because of an inflammatory band. Imaging studies may suggest hydatid cyst [7,8]. Imaging studies in our case showed a low-attenuation cystic lesion reported as an abscess or pseudoepancreatic cyst.…”
Section: Discussionmentioning
confidence: 85%
“…Albendazole is a useful drug for intraoperative spillage and to reduce the risk of recurrence. Ultrasoundguided percutaneous aspiration along with albendazole has also been described as an attractive alternative [8,9]. Nowadays, in the era of minimal invasive surgery, with advanced techniques, it can be excised laparoscopically also [10].…”
Section: Discussionmentioning
confidence: 99%
“…The location of RVHC can be subdivided into two categories, those developing chiefly in the greater peritoneal or abdominal cavity (cited as intraperitoneal type: 18 cases), and the others chiefly in the confined pelvic or lesser peritoneal cavity (cited as subperitoneal type: nine cases); the subperitoneal type was more liable to induce ureteral compression and more difficult to approach surgically . The predominant symptom due to RVHC was burning micturition (13 cases); physical examination revealed a pelvic mass in 17 patients and preoperative diagnosis was based on intravenous pyelography, ultrasonography (see also Ranzini et al 2002), CT (see also Yilmaz et al 2002), and serologic tests.…”
Section: Peritoneal Cavitymentioning
confidence: 99%